Evaluation of effectiveness of puzzle game on oral health related knowledge and behaviors among children - Majid Nameni; Mahmoud Tavousi; Mohammad Mehdi Naghibi Sistani; Hemat Gholinia (Payesh, 2019)
Objective (s): Edutainment (education through entertainment) could be effective in promoting knowledge and creating behavioral changes among children. This study aimed to evaluate the effectiveness of puzzle game on knowledge and oral health behavior of children. Methods: In this semi-experimented study 100 students of both genders were divided equally into two intervention and control groups. Then a “Healthy Mouth Puzzle” game was taught to the students of intervention group through a designed banner. Data were collected by self-designed questionnaires before and immediately after intervention, and at one-month follow-up. The data were analyzed performing t-test, and one way analysis of variance. Results: The mean score of knowledge before, immediately after and one month after the implementation of the intervention were found to be 8.92±1.50, 11.0±1.47 and 11.96±1.43 (P=0.0001) for  the intervention group. However in the control group, the difference of knowledge mean score was non significance in the three returns (P=0.43). The mean difference of knowledge between the two groups was not significant before the intervention (P=0.28), but the mean score of knowledge was higher in intervention group immediately after (P<0.001) and one month follow-up assessments (P<0.001). Positive Changes among children’s’ oral health behavior was not significant one month after intervention in both groups. Conclusion: Puzzle game improved the students’ oral health knowledge during short period but was ineffective to promote oral health behavior.